Business Feasibility Analysis of Shredded Layang Fish (Decapterus) at Thanko Shredded Fish Msmes - Pinky Natalia Samanta; Fenny Crista Anastasia Panjaitan; Gede Agus Surya Pratama (East Asian Journal of Multidisciplinary Research, 2023)
Shredded fish is a processed fishery product consisting of fish meat or seasoned, processed fish. This research aimed to analyse the business capital, profit, and feasibility of processing shredded Layang fish. This study was undertaken at Thanko Shredded Fish MSMEs in Jembrana, Bali from April to May 2022. The research employed observation of the process of shredded Layang from receiving raw materials to packaging and storing finished products. The data was analysis utilised cost, revenue, profit, efficiency and business risk analysis methods. The findings of this study indicated that the business of selling shredded Layang fish can generate business profits. The business has a capital of IDR. 57,501,093 and produces 2,880 packets of shredded Layang fish each year at a selling price of IDR. 25,000 per 100 grammes. An annual revenue of IDR 72,000,000 will generate a profit of Rp 14,498,907. With a selling price of IDR 25,000, the shredded Layang fish firm will Break Even Point or repay the money in less than a year if it can manufacture 2,290 units or more. The business feasibility research indicates that the shredded Layang fish business can be profitable with a payback period of less than one year.